Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) I: New additions of Homogryllacris Liu, 2007 from Guangxi and Yunnan - Liu, Jing; Yang, Dongdong; Bian, Xun (Zootaxa, 2021)
Based on the specimens of Homogryllacris deposited in the Guangxi Normal University, we describe two new species from Guangxi and Yunnan, China. Meanwhile, the morphological photographs and habitus of Homogryllacris brevispina Shi, Guo & Bian, 2012 and Homogryllacris gladiata Liu, 2007 are provided.